2017
DOI: 10.1159/000485313
|View full text |Cite
|
Sign up to set email alerts
|

A Trend in Sudden Sensorineural Hearing Loss: Data from a Population-Based Study

Abstract: This is the first study reporting on the incidence and clinical aspects of sudden sensorineural hearing loss (SSNHL) in South Korea. Using Health Insurance Review and Assessment Service data from 2011 to 2015, the monthly incidence of unilateral SSNHL and incidence according to patients’ sex, age, and month of diagnosis were investigated. The monthly incidence of unilateral SSNHL increased over the 5-year study period, with a mean annual incidence of 17.76 cases/ 100,000 of the population. The incidence increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…It remains unclear why female patients with CKD exhibited a significantly increased risk of SSNHL. However, another population-based study in South Korea showed that SSNHL has a slight female preponderance 24 ; thus, we thought our finding may be due to this different sex preponderance.…”
Section: Discussionmentioning
confidence: 63%
“…It remains unclear why female patients with CKD exhibited a significantly increased risk of SSNHL. However, another population-based study in South Korea showed that SSNHL has a slight female preponderance 24 ; thus, we thought our finding may be due to this different sex preponderance.…”
Section: Discussionmentioning
confidence: 63%
“…SSNHL is usually unilateral, with bilateral involvement accounting for less than 5% of the cases [ 3 ]. Recent population-based studies reported that the incidence of SSNHL ranges from 5 to 27 per 100,000 with a rapidly increasing annual incidence [ 4 , 5 ]. The inner ear hair cells are mainly responsible for transducing sound vibrations into electrical impulses, and then these electrical signals are transmitted by spiral ganglion neurons (SGNs) into the brainstem to have the hearing function [ 6 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 27 per 100,000 persons suffer from SSNHL in the United States each year. In Korea, the incidence of SSNHL was estimated to be approximately 17.76 per 100,000 persons per year 10 . The cause of SSNHL is elusive and multifactorial.…”
Section: Introductionmentioning
confidence: 99%